Rethinking confidence-building measures amid geopolitical rivalry - Ng, Joel (2024)
The US-China relationship has deteriorated over retaliatory measures each has inflicted on the other, but an under-appreciated fact is that tit-for-tat strategies contain their own solutions. However, because cooperation is not given as much weight as retaliation, confidence-building measures must be more ambitiously rethought to reverse spiralling distrust.